(3eUGHjM GdTQjYI GdfHhjI GdeMeOjI GdefJRY GdeNJGQ ef Ydhe CFeI GdRjOjIs - (3Yaja GdOjf Ydj Hf SdjeGf GdOhGQj GdfLQGfjs
(3ChdgG (B:s
(3GdMeO ddg aGdb GdMH hGdfhi CeG HYO , aEfg NW Ydi bdHi Cf CLeY ai GdTQjYI eNJUQkG s
(3BNQgG (B:s
(3BNQg ef (B" (3HGH PcQ GdeQJOjf hCMcGege (B" (3bhdg (B: (3bGd GdTjN hgh GdCbQH YfOfG Je GdcJGH HMeO Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3ChdgG Edi GdhQbI (B21(3C eced HNW eZGjQ HNW eGdcg Ydi MhGTjgG JYdjbGJ hebGHdGJs
(3cJHJ GdYfhGfGJ HNW eLhOs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs